The Influence of Word of Mouth Communication, Consumer Motivation, and the Environment in the Decision to Purchase Bottled Mineral Water for Housewives - Agustin Eka Rahmawati; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2022)
This study is based on the results of the researchers' observations and found word of mouth communication in community interactions, besides that consumer and environmental motivations are also seen in these interactions. This is because most of the housewives in RW 03 Celep Selatan Village are workers. Where they choose practical ways to fulfill household needs, one of which is by buying bottled mineral water. This research uses quantitative methods. The sample used was 186 housewives in RW 03 Celep Selatan using the purposive proportion random sampling method. Collecting data through the distribution of questionnaires and interviews with respondents and researcher observations. Data analysis used multiple regression based on SPSS 18.0 program. The results of this study indicate that there is a significant influence of word of mouth communication, consumer motivation, and the environment on the decision to purchase bottled mineral water simultaneously. Partially, word of mouth communication and the environment have a significant impact on the decision to purchase bottled mineral water. While consumer motivation does not have a significant effect partially on the decision to purchase bottled mineral water. Based on the results of the questionnaire, Cleo has 41% users, Aqua has 29% users, Club has 21% users, and Le Minerale has 7% users.